2019
DOI: 10.1101/765180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-trial dynamics of competing reach plans in the human motor periphery

Abstract: Contemporary theories of motor control have suggested that multiple motor commands compete for action selection. While most of these competitions are completed prior to movement onset, averaged saccadic eye movements that land at an intermediate location between two visual targets are thought to arise when a movement is initiated prior to the resolution of the competition. In contrast, while averaged reach movements have been reported, there is still debate on whether averaged reach movements are the result of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
(249 reference statements)
0
2
0
Order By: Relevance
“…Very soon after target emergence, muscle recruitment increased or decreased following target emergence to the right or left, respectively. Such lateralization is a hallmark of express visuomotor responses in humans (Pruszynski et al, 2010; Wood et al, 2015), and emphasizes that express visuomotor responses are tuned to stimulus location rather than being a generic startle or preparatory response (Gu et al, 2019; Selen et al, 2019). Another defining feature of express visuomotor responses in humans is the trial-by-trial consistency in which this initial change in muscle recruitment is more locked to target emergence rather than movement onset.…”
Section: Resultsmentioning
confidence: 99%
“…Very soon after target emergence, muscle recruitment increased or decreased following target emergence to the right or left, respectively. Such lateralization is a hallmark of express visuomotor responses in humans (Pruszynski et al, 2010; Wood et al, 2015), and emphasizes that express visuomotor responses are tuned to stimulus location rather than being a generic startle or preparatory response (Gu et al, 2019; Selen et al, 2019). Another defining feature of express visuomotor responses in humans is the trial-by-trial consistency in which this initial change in muscle recruitment is more locked to target emergence rather than movement onset.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, previous EMG work shown that humans can produce extremely fast stimulus-driven arm muscles responses that are inflexibly locked in space and time to visual stimuli (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), which were originally termed stimulus-locked responses (SLRs; 5). Specifically, the SLRs consistently encode the location of a visual stimulus within ~100ms from its presentation, irrespective of the mechanical RT.…”
Section: Introductionmentioning
confidence: 99%